Valor Percibido por el Cliente (VPC), como una herramienta para el análisis competitivo (2019)
This article addresses the perceived customer value (PCV) of a consumer durable product (refrigerators). It is a byproduct of the research project PERCEIVED CUSTOMER VALUE OF A CONSUMER DURABLE PRODUCT: CONSTRUCT AND MEASUREMENT, conducted by the same authors. After making some observations about the PCV, and some general comments about competitive analysis, the PCV figures resulting from the project, are shown. Finally, a way to use such figures as a tool for competitive analysis is illustrated.